Rendering of Verbal and Verbal-Visual Puns in Lithuanian-Dubbed Animated Film “Mr. Peabody and Sherman” - Brasienė, Brigita (Respectus Philologicus, 2024)
The rendering of verbal and verbal-visual puns in dubbing is a tough task that requires taking into account linguistic challenges, multimodal cohesion and dubbing synchronies. Thus, the aim of this research is to determine how verbal and verbal-visual puns are rendered from English into Lithuanian in the animated film Mr. Peabody & Sherman (2014). There have been collected 27 cases of puns including 14 verbal (52%) and 13 verbal-visual (48%) puns. The categorisation of verbal and verbal-visual puns according to the type revealed that verbal puns contained examples of homonymy, homophony and paronymy, but paronymic verbal puns prevailed the most. Almost all cases of verbal-visual puns were homonymic because of their intersemiotic construction which is usually based on polysemous words. All cases of verbal and verbal-visual puns have been rendered by employing 3 translation techniques: PUN→PUN, PUN→NON-PUN, PUN→PUNOID. The prevailing technique for transferring verbal and verbal-visual puns was PUN→PUN, which reveals the translator’s attempt to tackle linguistic challenges and consider multimodal cohesion and dubbing synchronies.
Keywords: audiovisual translation; dubbing; translation of puns; verbal puns; verbal-visual puns